Odpowiedź :
Odpowiedź:
[tex]-3:\frac{9}{10}+(-\frac{1}{5}):\frac{2}{3}=-\not3^1\cdot\frac{10}{\not9_{3}}-\frac{1}{5}\cdot\frac{3}{2}=-\frac{10}{3}-\frac{3}{10}=-\frac{100}{30}-\frac{9}{30}=-\frac{109}{30}=-3\frac{19}{30}\\\\\\-0,8:0,4+\frac{2}{3}\cdot(-1\frac{3}{4})=-2-\frac{\not2^1}{3}\cdot\frac{7}{\not4_{2}}=-2-\frac{7}{6}=-2-1\frac{1}{6}=-3\frac{1}{6}[/tex]
Odpowiedź:
-3:9/10+(-1/5):2/3=-3*10/9+(-1/5)×3/2=-10/3+(-3/10)=-100/30-9/30=-103/30
-0,8:0,4+2/3*(-1 3/4)= -8/10×10/4+2/3*(-7/4)=-2+(-7/6)=-3 1/6